Ratios of strange hadrons to pions in collisions of large and small nuclei - Oeschler, Helmut (The European physical journal. C, Particles and fields, 2017)
The dependence of particle production on the size of the colliding nuclei is analyzed in terms of the thermal model using the canonical ensemble. The concept of strangeness correlation in clusters of sub-volume VcVcV_c is used to account for the suppression of strangeness. A systematic analysis is presented of the predictions of the thermal model for particle production in collisions of small nuclei.